USE OF ELECTRONIC TOOL GEOGEBRA IN SOLVING PHYSICS PROBLEMS - Yermakova-Cherchenko Наталія (Journal of Information Technologies in Education (ITE), 2022)
Physics as one of the disciplines of the natural cycle has close ties with mathematics, which are manifested not only in the use of arithmetic operations and proportions, but also the functional dependence of physical quantities. In order to visualize mathematical operations, construct graphs and figures on the plane and in space, it is advisable to use various electronic software. The analysis of scientific and methodological literature made it possible to say that the electronic software is a separate application that contains a list of software modules and is aimed at the full organization of the educational process. GeoGebra is one of the many electronic software tools that provides ample opportunities for mathematics teachers and contributes to the quality organization of the educational process in mathematics. However, the experience of working with the electronic tool GeoGebra has shown a number of advantages of its use in the educational process in physics, which was confirmed by the results of a survey of physics teachers in Kherson. In their comments, some of the physics teachers mentioned the need to develop a methodology for using GeoGebra in solving physical problems in teaching certain topics. The article provides guidelines for using the electronic tool GeoGebra in solving problems in kinematics for physics teachers, which include: step-by-step instructions for registering and opening your own profile on GeoGebra, working with the application "Graphing Calculator", algorithm for plotting functional dependence of physical quantities , ways to enter the function and change individual parameters. The author highlights the method of using the electronic software GeoGebra in solving physics problems in teaching the topic "Graphs of the dependence of kinematic quantities on time for uniformly accelerated rectilinear motion" in 10th grade. Methods of solving typical problems in kinematics using the electronic software GeoGebra are presented.